Proposed ProModel Implementation to Increase Production Quantity at PT ABC - Diki Muchtar; Ramlan Yuniar Velani; Suci Tresna Dewi Handayani (Sekolah Tinggi Teknologi Wastukancana, 2025)
This study focuses on initiatives to enhance production quantity at PT ABC. The study applied a simulation-based approach using ProModel software to test various improvement scenarios without interfering with actual production activities. The data collected includes processing time at each workstation and machine capacity, which were used to build an accurate simulation model. The simulation results showed a significant increase in productivity from 35 to 78 units per hour after implementing the second improvement alternative involving additional manpower. This study offers practical and data-driven solutions to enhance production efficiency, reduce cycle time, and eliminate bottlenecks. The findings serve as a valuable reference for companies aiming to implement production line optimization strategies and simulation modeling to support continuous improvement in manufacturing performance.